Gold in the Perspective of Maqashidi's Interpretation - Azzah Nor Laila; Abdul Mustaqim; Muhammad Idlom Dzulqarnain (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This paper aims to find maqashid values ​​from the verses of the Quran about gold. The method used in this research is the maudhu'i interpretation with the maqashid interpretation approaches. The results of this research show that gold in the verses of the Qur'an is described in two categories. First, gold is an item or commodity treasure that has beauty and is valuable. In line with the meaning of gold as a precious metal that has a high and stable economic value. Gold as an item or one of the decorations that people tend to be interested in (Q.S. Ali Imran verse 14) and gold as a valuable item that tends to be a treasure to be stored or invested and should be issued zakat if it fulfils the nishab (Q.S. at-Taubah verse 34). Second, gold is jewellery for humans who inhabit heaven. Maqashid of the verses about the use of gold there are four maqashid namely hifzh al-mal, hifzh al-'irdl, hifzh ad-din, and hifzh nafs.